Overview of the Road Network Management System - Jan Mikolaj; Lubos Remek; Lubomir Pepucha (Communications - Scientific letters of the University of Zilina, 2014)
The long-term high standard research in civil engineering at the Department of Construction Management contributed to the fact that Slovakia succeeded to create its own pavement management system called Road Network Management System, which was accepted by international financial institutions on providing investment credits for rehabilitation of road network. At present, when the system has been in operation for more than 15 years, we can assess and analyse the results achieved in practice. This article presents a concise overview of the Road Network Management System. Computational details of pavement distress assessment and pavement structure evaluation are omitted, the focus lays on the decision making procedures for selection of appropriate repair action and process or priorization and optimization.